Black bone syndrome in chiken meat - Baldo, G a a; Paz, Ibiara Correia de Lima Almeida [UNESP]; Alves, M c f; Nääs, I a; Garcia, R g; Caldara, F r; Gavilan, C w s (Fundação APINCO de Ciência e Tecnologia Avícolas, 2013)
Black bone syndrome (BBS) affects poultry industry, and it is caused by the darkening of the tissue adjacent to the bone due to leak age of bone marrow contents during cooking. The objective of this experiment was to estimate BBS incidence in chicken thighs. A completely randomized experimental design, with two treatments (refrigerated or frozen) of 50 replicates each, was applied. The influence of BBS on meat quality was assessed according to bone lightness (*L), and meat appearance and sensorial characteristics. Lightness was measured using a colorimeter (Minolta® 410R) positioned on the proximal epiphyseal growth plate. Meat quality was evaluated after roasting by assigning scores for appearance (acceptable = no darkening, intermediate = little darkened, and unacceptable = severe darkening). Twelve refrigerated and 12 frozen thighs were used for sensorial analysis (adjacent muscle appearance, odor, tenderness, and flavor), assessed using a hedonic scale (1 = bad to 10 = very good) by trained panelists. Lightness was submitted to ANOVA and Tukey's test (p<0.05), and the Wilcoxon test (p<0.05) was used to analyze other characteristics. Confidence intervals were established for BBS based on *L values (<37.5=BBS and >37.5=normal). The incidence of BBS was 35%,with a 16%increase thighs were frozen. Meat taste was not influenced by the treatments. Meat appearance, flavor, and tenderness were not affected by freezing or refrigeration, only by BBS degree. It was concluded that freezing increases the incidence of BBS and chicken thighs with bones presenting lower luminosity have worse meat quality.
Keywords: Bone darkening; commercial processing plant; meat quality